Sportorthopädie | Sports Orthopedics - Memmert D; Rein R (Deutsche Zeitschrift für Sportmedizin)
In the past few years, there has been a real revolution in the field of match analysis. New approaches to evaluate performance have been developed especially in commercial football. This has been driven by novel developments in sensor technology and a changing coverage of sports games in media. Compared to analyses that depend on video material, positional data of individual players and the ball allow a much more in-depth analysis of sports games.Previously, performance analysis relied mainly on frequency distributions of certain game events. In contrast, the novel approaches allow calculating more complex metrics. This helps to measure and identify the performance of teams and individual players and especially how teams interact. However, the actual significance of many of these newer performance indicators has often not been sufficiently scientifically validated.To show how this can possibly be done, the present work introduces some new performance indicators in football where evidence has already been established. Furthermore, performance analysis is increasingly connected to the field of Big Data. Therefore, in addition this present paper introduces a model to connect Big Data and match analysis and illustrates the resulting implications regarding future training practices. KEY WORDS: Technological Developments, Football, Sport Games, Positional Data